Relationship Between Parents' Attention And Learning Motivation On The Trutching Behavior Of Private Madrasah Aliyah (MAS) Alwashliyah Tebing Tinggi City Students - Putri Handayani Nasution, Ade; Nur'aini, Nur'aini; Fadillah, Risydah (International Journal of Educational Research & Social Sciences, 2024)
Adolescence is a period of human development. This period is a period of change or transition from childhood to adulthood which includes biological changes, psychological changes, social changes. Truant behavior is one of the negative behaviors of students who often leave school or class without any clear reason. The aim of this research is to determine and analyze the relationship between parental attention and learning motivation and the expected behavior of Alwashliyah MAs students in Tebing Tinggi City. This research uses a quantitative research method, namely the method for collecting research data using a questionnaire with respondents to obtain information about the variables studied using a questionnaire. The research results show a significant negative relationship between parental attention and supportive behavior as seen from the coefficient value (Rxy) = -0.572 with p = 0.000 < 0.050. , the terminant coefficient (R2) value is 0.327, meaning that parental attention contributes 32.7% to students' correct behavior at MAs Alwashliyah, Tebing Tinggi City.